UNITED KINGDOM’S PRIMACY: ADDRESSING UK-ASEAN STRATEGIC PARTNERSHIPS IN THE ASIA-PACIFIC REGION THROUGH THE UK’S INDO-PACIFIC TILT OUTLOOK - Ryantono, Khansa Aqila; Avcu, Seyit Ali (Jurnal Asia Pacific Studies, 2024)
The Asia-Pacific region has played major role in global trade and for recent years becomes a very dynamic region where geopolitical and geostrategic shift take place. Competition and shift in political, economy and security dimension, along with growing global power presence in the region create a situation where countries with interest in the region should take actions needed to secure their national interest in the region. United Kingdom through the UK’s Indo-Pacific Tilt policy prioritizes stability in the region to support its geopolitical and geoeconomic ambition. The significance of the Indo-Pacific region for UK’s economy is very tremendous, hence, the emerging regional challenges that threats the stability in the region such as transnational crime and non-traditional security threats should be addressed accordingly. Pioneered at soft power as its diplomacy tool, United Kingdom is underpinning the importance of multifaceted cooperation with partners, countries, and regional actors to secure its national interest beyond its border. The strategic environment of ASEAN countries become vital to UK to realize and strengthen its ambition in the Indo-Pacific region. Multiple agendas in the key priorities’ areas are deployed through peaceful meaning between UK and ASEAN to bring peace, security, stability and prosperity as well as to ensure open, free and secure trading area in the Asia-Pacific region. Keywords: Indo-Pacific, Soft Power, The UK-ASEAN Strategic Partnerships, Geostrategic Shift.